Cartilage Regeneration - Tuan, Rocky S. (J Am Acad Orthop Surg, 2013)
Cartilage damaged by trauma has a limited capacity to regenerate. Current methods for treating small chondral defects include palliative treatment with arthroscopic debridement and lavage, reparative treatment with marrow stimulation techniques (e.g. microfracture), and restorative treatment, including osteochondral grafting and autologous chondrocyte implantation. Larger defects are treated by osteochondral allografting or total joint replacements. However, the future of treating cartilage defects lies in providing biologic solutions through cartilage regeneration. Laboratory and clinical studies have examined the treatment of larger lesions using tissue engineered cartilage. Regenerated cartilage can be derived from various cell types, including chondrocytes, mesenchymal stem cells, and pluripotent stem cells. Common scaffolding materials include proteins, carbohydrates, synthetic materials, and composite polymers. Scaffolds may be woven, spun into nanofibers, or configured as hydrogels. Chondrogenesis may be enhanced with the application of chondroinductive growth factors. Finally, bioreactors are being developed to enhance nutrient delivery and provide mechanical stimulation to tissue-engineered cartilage ex vivo. The multi-disciplinary approaches currently being developed to produce cartilage promise to bring the dream of cartilage regeneration in clinical use to reality.